Image Analysis on Individual Identification of Face Mask Monitoring Using Convolutional Neural Network. - et. al., Vidyullatha Pellakuri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Every person must put on a mask in this COVID-19 pandemic to protect himself. It came to practice that in the crowd of people wearing the mask in most public conventions such as Malls, Theatres, Parks. Whether or not a person with a mask is studying artificial intelligence. This study uses 7 deep learning algorithms that are highly used for real-time applications and the TensorFlow framework in the OpenCV library for model building through CNN in the Convolutionary neural network for face mask detection method. Through this model, every individual has emerged before they can join the public collecting the software 8 to search . To collect the data and evaluate the related features for the creation of a CNN prototype model to apply pre-processing concepts. To predict the outcomes of data using neural convolution networks and to visualize the results by building a dashboard in the Tableau open source visualization tool